Differentiation of convulsive syncope from epilepsy with an implantable loop recorder - Kanjwal, Khalil (Ivyspring International Publisher, 2009)
Introduction: Not all convulsive episodes are due to epilepsy and a number of these have a cardiovascular cause. Failure to identify these patients delays the provision of adequate therapy while at the same time exposes the individual to the risk of injury or death. Methods: We report on three patients who suffered from recurrent convulsive episodes, thought to be epileptic in origin, who were refractory to antiseizure therapy. Although each patient had undergone extensive evaluation, no other potential cause of his or her seizure like episodes had been uncovered. In each patient placement of an implantable loop recorder (ILR) demonstrated that their convulsive episodes were due to prolonged periods of cardiac asystole and/or complete heart block. In all patients their convulsive episodes were eliminated by permanent pacemaker implantation. Conclusion: In patients with refractory “seizure' like episodes of convulsive activity of unknown etiology a potential cardiac rhythm disturbance should be considered and can be easily evaluated by ILR placement.